PERAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DENGAN KEKERASAN (BEGAL) DI WILAYAH HUKUM POLRES DELI SERDANG - Maidin Gultom; Royen N. Lumbangaol (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This research aims to determine the factors causing the theft of motorized vehicles with violence in the Deli Serdang Police area and to determine the role of the police in tackling the crime of theft of motorized vehicles with violence in the Deli Serdang Police area. The data used in this research are primary data and secondary data. Primary data in the form of interviews with Mr. Kompol Risqi Akbar, S.I.K.M.H. as Head of Criminal Investigation Unit of Deli Serdang Police Station. Secondary data is data obtained from library materials both books, laws and regulations, the internet and writings related to the problems studied by quoting, reading, and analyzing. The analysis is carried out qualitatively while, the conclusion is drawn using the deductive thinking method. The results of this study indicate that the factors causing the theft of motorized vehicles with violence in the Deli Serdang Police District are economic factors that force people to fulfill their needs but it is difficult to get money such as poverty, unemployment, and layoffs, environmental factors are factors that are broader in scope there is a family environment and community association, educational factors that are a means for someone to know which ones are good and bad, factors of intention and opportunity, and social and cultural factors that change traditional habits into modern ones. The role of the police in tackling the crime of theft of motorized vehicles with power is divided into preventive (prevention) and repressive (prosecution).